2021
DOI: 10.3390/machines10010013
|View full text |Cite
|
Sign up to set email alerts
|

Power Conversion Techniques Using Multi-Phase Transformer: Configurations, Applications, Issues and Recommendations

Abstract: Recently, the superiority of multi-phase systems in comparison to three-phase energy systems has been demonstrated with regards to power generation, transmission, distribution, and utilization in particular. Generally, two techniques, specifically semiconductor converter and special transformers (static and passive transformation) have been commonly employed for power generation by utilizing multi-phase systems from the available three-phase power system. The generation of multi-phase power at a fixed frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…These, make the 10-pulse using three-limbed three-to-five transformer advantageous over the conventional 6-pulse rectifier in applications such as traction rectifier. Further, the rectifiers using 3-to-m phase transformer are useful to enhance the quality the output DC voltage [37]. Improving the conventional transformer efficiency is a substantial aim of scientific research.…”
Section: Experimental and Simulation Resultsmentioning
confidence: 99%
“…These, make the 10-pulse using three-limbed three-to-five transformer advantageous over the conventional 6-pulse rectifier in applications such as traction rectifier. Further, the rectifiers using 3-to-m phase transformer are useful to enhance the quality the output DC voltage [37]. Improving the conventional transformer efficiency is a substantial aim of scientific research.…”
Section: Experimental and Simulation Resultsmentioning
confidence: 99%
“…Proposals have previously been presented, in which a hybrid controller with fuzzy logic and GAs was designed. They achieve the desired objectives in the systems and improve their performance against nonlinear behaviors [5,[28][29][30]. These techniques have also proven to be effective in counteracting disturbances and changes in the initial conditions of the process.…”
Section: Related Workmentioning
confidence: 99%
“…Fault analysis of a multiphase transmission line is essential for the successful deployment of a multiphase transmission line protection system design [9]. The study of an unbalanced three-phase system and the effect of an unbalanced supply on the three-phase induction machines is expansively reported in the literature [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from complexity, load mismatch is also seen. In the lower side n‐ phase system (excluding phase multiple of three) it was found that the seven‐phase system has the lowest mismatch of 2.3% [9].…”
Section: Introductionmentioning
confidence: 99%